Meta-Analysis: Effect of Hyperbaric Oxygen Therapy on Diabetic Foot Ulcer Recuperation - Faried, Faried Effendi Surono; Tamtomo, Didik Gunawan (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Diabetes mellitus (DM) is a global phenomenon due to the high morbidity and mortality, especially in developing countries such as Indonesia. An ulcer is a wound and is usually found in patients who experience increased blood sugar and can cause peripheral blood vessel disorders, blood vessel disorders will result in peripheral neuropathy or a combination of both, diabetic ulcers are a condition often experienced by diabetes sufferers. Hyperbaric Oxygen Therapy (HBOT) is a therapy that is considered effective in healing diabetic ulcers and has been proven by many studies conducted. This study aims to analyze the effect of HBO therapy on the improvement of diabetic ulcer wounds. Subjects and Method: This was a systematic review and meta-analysis of primary studies. Article searches were carried out based on the PICO model. Population: diabetic ulcer patients. Intervention: Hyperbaric Oxygen Therapy. Comparison: placebo. Outcome: diabetic ulcers condition. Article searches were carried out from Google Scholar, MEDLINE/PubMed, Science Direct, Scopus, Hindawi, BMC, and Spinger Link databases. Keywords used